Wagnerallusioner i Wilhelm Peterson-Bergers Ran - Tillman, Joakim (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2008)
Wagnerian allusions in Wilhelm Peterson-Berger’s Ran Many claims have been made about imitation of Wagner’s style and use of Wagnerian methods in Peterson-Berger’s music drama Ran (1903). However, no one has mentioned the important allusions to specific Wagner works. Departing from J. Peter Burkholder’s typology of musical borrowing, the first aim of this article is to analyse these allusions. The second aim is to examine the allusions in the context of ”notions of creativity, inspiration, and originality; the constraints of tradition and innovation; musical listening and the audience for allusion; the relationship between criticism and composition” (Reynolds 2003:xi). One crucial question is how Peterson-Berger’s frequent statements about the importance of originality can be reconciled with his own borrowings in Ran. While he rejected stylistic imitation, an examination of his opinions suggests that he accepted allusions if they were not too obvious. Even though the allusions in Ran are to works in the same genre and often appear in similar dramatic contexts, they are transformed and condensed. As most of Wagner’s later works had not been played in Sweden at the time of Ran’s first performance, his allusions seem not to have been intended for the general audience. Peterson-Berger considered Wagner the foundation for the future development of music. However, in a kind of Bloomian misreading of Wagner he demanded completions, revisions, and correction of excesses. The Wagnerian allusions in Ran seem to be a bold and defiant way for Peterson-Berger to demonstrate that he carried on the Wagnerian inheritance, but that he had mastered and incorporated the Wagnerian elements in a personal style that made a genuine Swedish music drama possible.